Implementation of WASH (Water, Sanitation, and Hygiene) with Stunting Incidents in Pujer District, Bondowoso Regency - Dariswan, Dinda Tiara Nurzahrah; Nurika, Globila (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
The Government of Indonesia is working with the United Nations International Children's Emergency Fund (UNICEF) to support a development program for the Water, Sanitation, and Hygiene (WASH) sector. Globally, access to WASH is still inadequate, and diseases resulting from poor WASH contribute to 13% of under-five deaths. Poor sanitation can cause various diseases, including nutritional problems such as stunting. In 2021, Bondowoso will become one of the 10 regencies or cities with the most considerable prevalence of stunting under five in East Java. Therefore, it is essential to research and examine the link between the success of WASH implementation and the stunting rate in Pujer District, Bondowoso Regency. This quantitative descriptive study was conducted in the Pujer District with 67 respondents using a simple random sampling technique. The study used several variables, including the hygiene behaviour of mothers under five, the ownership of access to family sanitation, the physical quality of family drinking water, the incidence of infectious diseases (diarrhoea) in children, and the nutritional status of children based on height and age (TB/U). The analyses were univariate, crosstab, and scoring. There were 16 families (24.4%) with an unsuccessful WASH assessment but no stunting below five, and 33 families (49.25%) with a successful WASH assessment but no stunting below five. It was concluded that the better the WASH was applied, the better the nutritional status of the toddlers; conversely, the worse the WASH was implemented, the worse the nutritional status of the toddlers.